2017
DOI: 10.1093/jpepsy/jsx133
|View full text |Cite
|
Sign up to set email alerts
|

Parental Perceptions of Child Vulnerability in Families of Youth With Spina Bifida: the Role of Parental Distress and Parenting Stress

Abstract: For parents of youth with SB, personal distress, and parenting stress are related to parental perceptions of child vulnerability, and child age may moderate this relationship. Parental personal distress and parenting stress are important targets for future interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
(53 reference statements)
1
8
0
Order By: Relevance
“…In this cohort, most parents, including the three mothers that were diagnosed with mental health issues, reported adjusting adequately to their new situation, regardless of the individual outcome. Hope, parenting satisfaction, income, marital adjustment, economical resources and (social) support are factors improving parental psychological adjustment in parents of children with SB, in contrast to disability related stress, negative family impact and negative coping strategies 41 . In this cohort, parental hopes, parenting satisfaction, and their social support network may have positively contributed to this early adjustment.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In this cohort, most parents, including the three mothers that were diagnosed with mental health issues, reported adjusting adequately to their new situation, regardless of the individual outcome. Hope, parenting satisfaction, income, marital adjustment, economical resources and (social) support are factors improving parental psychological adjustment in parents of children with SB, in contrast to disability related stress, negative family impact and negative coping strategies 41 . In this cohort, parental hopes, parenting satisfaction, and their social support network may have positively contributed to this early adjustment.…”
Section: Discussionmentioning
confidence: 72%
“…Earlier studies have reported depression and anxiety in patients undergoing fetal diagnosis or receiving fetal therapy, suggesting that women underdoing MFS require appropriate follow‐up and support to detect increased risks of mood and anxiety disorders 37‐39 . This was already the case in women with fetal SB in the pre‐fetal surgery era, 40,41 to which the stress of the MFS and potential complications of prematurity is now added.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were recruited for an ongoing longitudinal study examining family and peer relationships, neuropsychological functioning, and psychological adjustment of families of youth with SB. 8 The present study’s analyses focus on the first three time points: Time 1(baseline; youth age 8–15 years), Time 2 (2 years after baseline; youth age 10–17 years), and Time 3 (4 years after baseline; youth age 12–19 years). Families of youth with SB were recruited from four Midwestern hospitals, a statewide SB association, in person at regularly scheduled clinic visits, and through recruitment letters.…”
Section: Methodsmentioning
confidence: 99%
“…Parent personal distress is operationalized as the degree of overwhelming sadness, anxiety, or pain experienced by an individual (who is also a parent). 89 Parents of youth with SB have been found to experience clinical levels of personal distress. 10 However, it is unclear how the experience of personal distress by a parent affects youth adjustment, specifically HRQOL.…”
mentioning
confidence: 99%
See 1 more Smart Citation